Reading slowly : a Festschrift for Jens E. Braarvig - Edzard, Lutz; Borgland, Jens W.; Hüsken, Ute; Braarvig, Jens (Harrassowitz Verlag, 2018)
Reading Slowly' contains contributions from a variety of fields as diverse as Buddhist Studies, Linguistics, Middle Eastern Studies, Indology, East Asia Studies, Sinology, Classical Studies and Nordic Studies, all focused in some way on the importance of philological scholarship for understanding history, culture, religion, language and law. Although their objects of study, source language(s), media, focus and research questions are different, the essays in this volume are firmly bound together by the philological method?in the broadest sense of the term?and the scholarship of Jens E. Braarvig, whose vast scope of interest and knowledge is reflected in the breadth of this Festschrift.